ANALISIS DAN PERANCANGAN SISTEM INFORMASI KEUANGAN RETRIBUSI PADA BADAN KEUANGAN DAERAH PROVINSI JAMBI - hadi, Irzan; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2019)
Regional levies are an important source of regional income to finance the implementation ofgovernmentand regional development and to improve service to the community and regionalindependence, that in theframework of implementing regional levies collection techniques needto be regulated as a guideline forcollection agencies in accordance with their duties. Retributionthat is currently running at the JambiProvincial Finance Agency which while in the process ofretribution revenue is still manuallyexperiencing several obstacles such as inaccurate datareported that must wait for all the OPDs of JambiProvince to take a long time which causesdelays to the Regional Finance Agency Jambi Province incalculating the results of the Jambiprovincial retribution income ... to resolve constraints is a system thatis capable of processingdata. Here the author designed a new financial information system for levies,while theinformation recommended for Jambi provincial financial institutions consists of admintables,Retribution Tables, Tourist Tables, Tourist Officer Tables, Visitor Tables, Visit Tables